Development of universal standards for methodological-oriented physics training in technical university; Journal of International Scientific Publication: Educational Alternatives; Vol. 9, pt. 3 - Larionov V. V. Vitaliy Vasilyevich (2011, 2011)
Материалы II Международной конференции "Образование, исследования и развитие", Солнечный берег, Болгария, 9-13 сентября 2011 г.